Modified POSS (Polyhedral Oligomeric Silsesquioxane) and derivative flame-retardant synergist thereof, preparation method thereof, thermoplastic polyester elastomer material and preparation method thereof
By using modified POSS and its derivatives as flame retardant synergists in thermoplastic polyester elastomer materials, combined with phosphorus-based and nitrogen-based flame retardant, the problems of poor flame retardant and insufficient physical and mechanical properties of the material are solved, and efficient flame retardant and drip-proof effects are achieved.
Patent Information
- Application Number
- CN202411992721.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
The problems of poor flame retardancy, poor physical and mechanical properties of thermoplastic polyester elastomer materials and dripping during combustion.
Modified POSS and its derivatives are used as flame retardant synergists, and the amount of flame retardant is reduced and the flame retardant performance of the material is improved by synergistically acting with phosphorus and nitrogen flame retardant. The modified POSS and its derivatives form a carbon layer, a ceramic barrier layer, a protective film or a thermally insulated coke layer during combustion to prevent dripping and isolate heat and oxygen.
It significantly improves the flame retardant performance, drip resistance and physical and mechanical properties of thermoplastic polyester elastomer materials, ensuring that the material is not prone to cracking under high temperature conditions and maintains good processing performance.
Smart Images

Figure CN119751883A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of thermoplastic polyester elastomer materials, and in particular to a flame retardant synergist of modified POSS and its derivatives and a preparation method thereof, a thermoplastic polyester elastomer material and a preparation method thereof. Background Art
[0002] Polyhedral oligomericsilsesquioxane (POSS) is a special organic amorphous material. It is a polycyclic organic monomer composed of a silicon framework and its embedded oxygen atoms. It is an inorganic-organic hybrid nanomaterial. The inorganic silicon cage core in POSS decomposes under heat to form a dense ceramic barrier layer, which isolates the release of combustible gas and the entry of external heat into the interior, thereby delaying further decomposition of the material. POSS shows great application potential in the field of flame retardants.
[0003] Thermoplastic polyester elastomer (TPEE) has excellent mechanical properties, wear resistance, oil resistance and excellent elasticity. It is widely used in shoe materials, pipes, tires, membrane materials and cable materials. my country's TPEE resin mainly relies on imports, and the modification technology is also in the early stages of development. Due to the characteristics of thermoplastic polyester elastomer materials, too much flame retardant cannot be added, otherwise the mechanical properties will be lost too much and it is easy to crack during use. Therefore, it is very necessary to develop a new halogen-free thermoplastic polyester elastomer material that has halogen-free high flame retardancy, anti-drip effect, high physical and mechanical properties and anti-cracking performance. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the present invention proposes a modified POSS and its derivative flame retardant synergist and a preparation method thereof, a thermoplastic polyester elastomer material and a preparation method thereof, aiming to solve the problems of poor flame retardancy, poor physical and mechanical properties and dripping during combustion of the current thermoplastic polyester elastomer material.
[0005] To achieve the above-mentioned purpose, the present invention provides a modified POSS and its derivative flame retardant synergist and a preparation method thereof, a thermoplastic polyester elastomer material and a preparation method thereof. A modified POSS and its derivative flame retardant synergist, characterized in that the structure of the modified POSS and its derivative flame retardant synergist is:
[0006] Wherein, R is a non-reactive group, such as isobutyl, isooctyl, ethyl, cyclohexyl, cyclopentyl, or phenyl, and R1 is n-propyl or phenylene; R2 is a cyclic structure with a carbon-to-hydrogen ratio greater than 1, including at least one of a benzofuran group and a polycyclic aromatic group.
[0007] Optionally, the benzofuran group includes at least one of a benzofuran group and a dibenzofuran group.
[0008] Optionally, the polycyclic aromatic group includes at least one of a naphthalene ring group, an anthracene ring group, a phenanthrene ring group, an acenaphthene ring group, a fluorene ring group and a perylene ring group.
[0009] A method for synthesizing a modified POSS and its derivative flame retardant synergist, which is prepared by dehydration reaction of compound 1 and compound 2 under the action of a catalyst, characterized in that the reaction route is as follows:
[0010] Optionally, the molar ratio of compound 1 to compound 2 is 2:1.
[0011] Optionally, the catalyst includes at least one of an acidic catalyst, a metal catalyst, a basic catalyst and an organic catalyst, and the solvent is an organic solvent, including at least one of alcohols, aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, ethers, ketones and diol derivatives.
[0012] A thermoplastic polyester elastomer material, characterized in that the ingredients of the thermoplastic polyester elastomer material, measured in parts by weight, include: 80-120 parts of thermoplastic polyester elastomer, 2-12 parts of the above-mentioned modified POSS and its derivative flame retardant synergist, 1-10 parts of P series flame retardant, and 1-10 parts of N series flame retardant.
[0013] Optionally, the ingredients of the thermoplastic polyester elastomer material include, by weight: 80-120 parts of thermoplastic polyester elastomer, 2-12 parts of the modified POSS and its derivative flame retardant synergist as described above, 4-7 parts of P series flame retardant, and 4-7 parts of N series flame retardant.
[0014] Optionally, the thermoplastic polyester elastomer includes at least one of a polyester-type thermoplastic polyester elastomer or a polyether-type thermoplastic polyester elastomer.
[0015] Optionally, the P series flame retardant includes an inorganic phosphorus flame retardant or an organic phosphorus flame retardant, the inorganic phosphorus flame retardant includes at least one of red phosphorus, phosphate, and polyphosphate; the organic phosphorus flame retardant includes at least one of phosphate ester, phosphite, and phosphine oxide; and / or the N series flame retardant includes at least one of melamine urate, melamine phosphate, and melamine inorganic acid salt.
[0016] Optionally, the ingredients of the thermoplastic polyester elastomer material also include at least one of a lubricant and an antioxidant; wherein, the ingredients are calculated in parts by weight, the lubricant is 0.5-1 part, and the antioxidant is 0.5-1 part.
[0017] A preparation method of a thermoplastic polyester elastomer material, characterized in that it comprises the following steps: obtaining a modified POSS and a flame retardant synergist of its derivatives through a dehydration reaction; uniformly mixing the ingredients, performing banburying, extrusion and granulation to obtain a granular material; and obtaining the thermoplastic polyester elastomer material through drying the granular material.
[0018] Optionally, the ingredients also include at least one of a lubricant and an antioxidant.
[0019] The beneficial effects of the present invention are as follows: the present invention contains cage-like macromolecules POSS and cyclic structure groups with a carbon-hydrogen ratio greater than 1. Since the flame retardant synergist of the modified polyhedral oligomeric silsesquioxane and its derivatives contains boron, a cyclic structure R2 with a carbon-hydrogen ratio greater than 1, and two inorganic silicon cage cores, the boron element forms boric acid during combustion, and the boric acid dehydrates and carbonizes the surface of the material to form a carbon layer; the two inorganic silicon cage cores are decomposed by heat to form a dense ceramic barrier layer, isolating the release of combustible gas and the entry of external heat into the interior; the cyclic structure R2 with a carbon-hydrogen ratio greater than 1 has a high The carbon-hydrogen ratio of the benzofuran group and the polycyclic aromatic group contains a large amount of carbon elements. A large amount of carbon elements will form a glass-like protective film or an insulating coke layer during the combustion process. These protective films or coke layers can isolate the air, prevent the transfer of heat, and reduce the release of combustible gases. These structures form protective layers such as carbon layers, ceramic barrier layers, protective films or insulating coke layers during the combustion process, which greatly improves the anti-drip effect. At the same time, they isolate heat and oxygen transfer and reduce the release of combustible gases. The combined effect of multiple mechanisms significantly improves the flame retardant properties of the material. Furthermore, the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergists cooperate with the phosphorus flame retardant that provides the acid source and the nitrogen flame retardant that provides the gas source to synergize and flame retardant, thereby reducing the amount of flame retardant and improving the flame retardant properties of the material.
[0020] The modified polyhedral oligomeric silsesquioxane and its derivative synergistic flame retardant contains a large amount of silicon and oxygen elements. During the combustion of the polymer, it forms phosphate with the acidic gas after the phosphorus flame retardant is burned, which promotes the reaction between the phosphorus element and the polymer, thereby quickly forming a carbon layer. The SiO2 generated after the combustion of the modified polyhedral oligomeric silsesquioxane and its derivative synergistic flame retardant is interspersed in the coke layer, similar to the role of sand in cement, making the coke layer more stable. The coke layer makes it difficult for heat to penetrate the condensed phase, preventing oxygen from entering the combustion area and the gaseous or liquid products generated by degradation from overflowing the surface of the material. The boron in the modified polyhedral oligomeric silsesquioxane and its derivative synergistic flame retardant has a 2Pz empty orbital that can accept lone pairs of electrons and can produce a synergistic effect by coordinating with phosphorus. The synergistic effect of boron and phosphorus makes the above reaction faster. At the same time, the combustion of the nitrogen flame retardant produces a large amount of non-combustible gas, which causes the system in the molten state of the incompletely carbonized part of the TPU to foam, causing the burning polymer to produce a large number of pores. At the same time, the organic matter continues to react, dehydrate and carbonize to form inorganic matter and carbon residue. When the reaction is completed, the system gels and solidifies, and finally forms a porous foam carbon layer.
[0021] The present invention also uses the modified POSS and its derivative flame retardant synergist to prepare thermoplastic polyester elastomer materials. In the present invention, the thermoplastic polyester elastomer does not need to add a plasticizer, has good elasticity, chemical resistance and wear resistance, etc., and together with the modified POSS and its derivative flame retardant synergist, P series flame retardant and N series flame retardant are used as the main components of the thermoplastic polyester elastomer material. The components cooperate and synergize with each other. During the combustion process, the Si element and the C element in the R2 group can react rapidly to generate a large number of Si-C bonds. At the same time, the B element can form a glass film on the surface of the thermoplastic polyester elastomer material, and the generated boric acid can rapidly dehydrate the polymer to produce a carbon layer. The B element in the modified POSS and its derivative synergistic flame retardant can also coordinate with the P element in the system to produce a synergistic effect, thereby improving the flame retardant effect. By adding the modified POSS and its derivative synergist The flame retardant works synergistically with the P-series and N-series flame retardants to quickly produce a harder carbon layer to prevent the thermoplastic polyester elastomer from burning and dripping, and isolate the air to improve the flame retardancy of the thermoplastic polyester elastomer material. The P-series flame retardant provides an acid source, the N-series flame retardant provides a gas source, and the modified POSS and its derivative synergistic flame retardant provide a rich carbon source, so that the P-series flame retardant and the N-series flame retardant exert stronger flame retardancy. The prepared thermoplastic polyester elastomer material can ensure the original good processing performance, elasticity and flame retardancy of the thermoplastic elastomer, and improve the anti-cracking performance, flame retardancy and physical and mechanical properties of the thermoplastic polyester elastomer material. The modified POSS and its derivative flame retardant synergist is in the state of a colorless viscous liquid. When added to the thermoplastic polyester elastomer material, it has little effect on the performance of the thermoplastic polyester elastomer material, and a thermoplastic polyester elastomer material with excellent flame retardancy can be obtained without a very high addition amount. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The molecular structure diagram of the modified POSS and its derivative flame retardant synergist of the present invention. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0024] Unless defined otherwise, all technical and scientific terms used herein have the common meaning in the art to which the claimed subject matter belongs.
[0025] In order to facilitate the understanding of this embodiment, the symbols, instruments and terms are explained below: Thermoplastic Polyester Elastomer: Thermal Plastic Shielding, TPEE, has good thermal stability and dimensional stability, can maintain stable performance at high temperatures, and is widely used in electronics, automobiles, aerospace and other fields to protect electronic equipment from high temperatures or electromagnetic interference.
[0026] POSS: A special cage structure and organic-inorganic hybrid system, mainly used for chemical modification / doping modification of other materials to improve the performance of raw materials, such as improving heat resistance, mechanical strength, and air permeability, etc. It can also be multifunctional.
[0027] P series flame retardants: Phosphorus series flame retardants include inorganic phosphorus series flame retardants and organic phosphorus series flame retardants.
[0028] N series flame retardant: nitrogen series flame retardant.
[0029] Thermoplastic polyester elastomer (TPEE) has excellent mechanical properties, wear resistance, oil resistance and excellent elasticity. It is widely used in footwear, pipes, tires, membrane materials and cable materials. my country's TPPE resin mainly relies on imports, and the modification technology is also in the early stages of development. The Chinese invention patent with application number CN 202010194223.1 discloses a rubber molding method and rubber, which utilizes vinyl polydimethylsiloxane, 1,2,3,4,5-pentafluoro-6-[(1,2,2-trifluorovinyl)oxy]-benzene (CAS: 653-26-9), (E)-3-(2- A new type of rubber is synthesized with (1H-tetrazolyl-5-yl)vinyl)-6-fluoro-1H-indole (CAS: 1316695-35-), 4-(trifluorovinyloxyphenyl)boric acid (CAS: 213701-14-5), coupling agent, octa-p-aminophenyl-POSS and carbon fiber as the main materials. The flame retardancy of the rubber is improved by using the halogen-containing structure. However, halogens will release harmful gases such as halogenated diphenyl ethers (PBDE) at high temperatures, which will cause potential harm to human health and the environment and may even induce cancer. Due to the characteristics of thermoplastic polyester elastomer materials, too much flame retardant cannot be added, otherwise the mechanical properties will be lost too much and it is easy to crack during use. Therefore, it is very necessary to develop a new type of halogen-free thermoplastic polyester elastomer material with high flame retardancy, anti-drip effect, high physical and mechanical properties and anti-cracking performance.
[0030] To solve the above problems, the present invention provides a modified POSS and its derivative flame retardant synergist, characterized in that the structure of the modified POSS and its derivative flame retardant synergist is:
[0031] Among them, R is a non-reactive group, such as isobutyl, isooctyl, ethyl, cyclohexyl, cyclopentyl, or phenyl, R1 is n-propyl or phenylene; R2 is a cyclic structure with a carbon-hydrogen ratio greater than 1, including at least one of a benzofuran group and a polycyclic aromatic group.
[0032] The present invention comprises a cage-like macromolecule POSS and a cyclic structure group with a carbon-to-hydrogen ratio greater than 1. Since the flame retardant synergist of the modified polyhedral oligomeric silsesquioxane and its derivatives contains a boron element, a cyclic structure R2 with a carbon-to-hydrogen ratio greater than 1, and two inorganic silicon cage cores, the boron element forms boric acid during combustion, and the boric acid dehydrates and carbonizes the surface of the material to form a carbon layer; the two inorganic silicon cage cores are decomposed by heat to form a dense ceramic barrier layer, isolating the release of combustible gas and the entry of external heat into the interior; the cyclic structure R2 with a carbon-to-hydrogen ratio greater than 1 has a high carbon-to-hydrogen ratio , benzofuran groups and polycyclic aromatic groups contain a large amount of carbon elements, which will form a glassy protective film or an insulating coke layer during the combustion process. These protective films or coke layers can isolate the air, prevent the transfer of heat, and reduce the release of combustible gases. These structures form protective layers such as carbon layers, ceramic barrier layers, protective films or insulating coke layers during the combustion process, which greatly improves the anti-drip effect. At the same time, they isolate heat and oxygen transfer and reduce the release of combustible gases. The combined effect of multiple mechanisms significantly improves the flame retardant properties of the material. Furthermore, the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergists cooperate with the phosphorus flame retardant that provides the acid source and the nitrogen flame retardant that provides the gas source to synergize and flame retardant, thereby reducing the amount of flame retardant and improving the flame retardant properties of the material.
[0033] Further, the benzofuran group includes at least one of a benzofuran group and a dibenzofuran group.
[0034] Benzene has a high carbon content and a high carbon-to-hydrogen ratio, which can slow down the spread of flames during combustion. When the flame is removed, it can quickly extinguish itself, reducing the duration and intensity of combustion. The furan group has a high carbon content and contains oxygen elements that do not participate in combustion. The combination of the two forms a benzofuran group or dibenzofuran group that has both a high carbon-to-hydrogen ratio and a low combustion element. The two work together to form a glass-like protective film or an insulating coke layer during the combustion process. These protective films or coke layers can isolate the air and prevent heat transfer, while reducing the content of combustibles and indirectly promoting carbonization.
[0035] In some embodiments, R2 is preferably a benzofuranyl group.
[0036] Further, the polycyclic aromatic group includes at least one of a naphthalene ring group, an anthracene ring group, a phenanthrene ring group, an acenaphthene ring group, a fluorene ring group and a perylene ring group.
[0037] In some embodiments, R2 is preferably a naphthyl ring group.
[0038] The present invention also provides a method for synthesizing a modified POSS and its derivative flame retardant synergist, which is prepared by dehydration reaction of compound 1 and compound 2 under the action of a catalyst, characterized in that the reaction route is as follows:
[0039] Furthermore, the steps of the synthesis method of modified POSS and its derivative flame retardant synergist are as follows: firstly dissolving compound 1 in an organic solvent solution, then adding a catalyst, adding an aqueous solution of compound 2 under the action of the catalyst, carrying out a catalytic reaction, and then washing and drying to obtain modified POSS and its derivative flame retardant synergist.
[0040] Furthermore, the molar ratio of compound 1 to compound 2 is 2:1.
[0041] The spatial structure of compound 1 polyhedral oligomeric silsesquioxane is relatively large, and it is necessary to ensure that the spatial steric hindrance is small enough in the reaction so that the modified POSS and its derivative flame retardant synergist can be obtained. During the reaction, each compound 2 connects 2 compounds 1, that is, the molar ratio of compound 1 to compound 2 is 2:1, which ensures sufficient space for compound 3 and achieves structural stability in compound 3. Compound 2 contains 2 hydroxyl groups, and each hydroxyl group is combined with the amino group for dehydration reaction to obtain compound 3, that is, the modified POSS and its derivative flame retardant synergist. The overall reaction requires a single substance, is simple to operate, and is easy to achieve.
[0042] In some embodiments, compound 1 is preferably aminopropyl heptaisobutyl caged polysilsesquioxane.
[0043] In some embodiments, compound 1 is preferably aminophenyl heptaisobutyl cage polysilsesquioxane.
[0044] In some embodiments, the structural formula of compound 3 is: The following is calculated as modified POSS flame retardant synergist 1
[0045] In some embodiments, compound 2 is preferably benzo[B]naphtho[2,3-D]furan-2-hydroxyboronic acid.
[0046] In some embodiments, compound 2 is preferably dibenzofuran-3-boronic acid.
[0047] In some embodiments, the structural formula of compound 3 is: The following is calculated as modified POSS flame retardant synergist 2
[0048] Furthermore, the catalyst includes at least one of an acidic catalyst, a metal catalyst, a basic catalyst and an organic catalyst, and the solvent is an organic solvent including at least one of alcohols, aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, ethers, ketones and diol derivatives.
[0049] In some embodiments, the catalyst is preferably acetic acid.
[0050] In some embodiments, the solvent is preferably ethanol.
[0051] The present invention also uses the modified POSS and its derivative flame retardant synergist to prepare a thermoplastic polyester elastomer material. The ingredients of the thermoplastic polyester elastomer material, measured by weight, include: 80-120 parts of thermoplastic polyester elastomer, 2-12 parts of modified POSS and its derivative flame retardant synergist, 1-10 parts of P series flame retardant, and 1-10 parts of N series flame retardant.
[0052] The present invention uses the modified POSS and its derivative flame retardant synergist to prepare a thermoplastic polyester elastomer material. In the present invention, the thermoplastic polyester elastomer does not need to add a plasticizer and has good elasticity, chemical resistance, wear resistance and other properties. The modified POSS and its derivative flame retardant synergist, P series flame retardant and N series flame retardant are used as the main components of the thermoplastic polyester elastomer material. The components cooperate with each other and act synergistically. During the combustion process, the Si element and the C element in the R2 group can react rapidly to generate a large number of Si-C bonds. At the same time, the B element can form a glass film on the surface of the thermoplastic polyester elastomer material, and the generated boric acid can rapidly dehydrate the polymer to produce a carbon layer. The B element in the modified POSS and its derivative synergistic flame retardant can also coordinate with the P element in the system to produce a synergistic effect, thereby improving the flame retardant effect. By adding the modified POSS and its derivative synergist The flame retardant works synergistically with the P-series and N-series flame retardants to quickly produce a harder carbon layer to prevent the thermoplastic polyester elastomer from burning and dripping, and isolate the air to improve the flame retardancy of the thermoplastic polyester elastomer material. The P-series flame retardant provides an acid source, the N-series flame retardant provides a gas source, and the modified POSS and its derivative synergistic flame retardant provide a rich carbon source, so that the P-series flame retardant and the N-series flame retardant exert stronger flame retardancy. The prepared thermoplastic polyester elastomer material can ensure the original good processing performance, elasticity and flame retardancy of the thermoplastic elastomer, and improve the anti-cracking performance, flame retardancy and physical and mechanical properties of the thermoplastic polyester elastomer material. The modified POSS and its derivative flame retardant synergist is in the state of a colorless viscous liquid. When added to the thermoplastic polyester elastomer material, it has little effect on the performance of the thermoplastic polyester elastomer material, and a thermoplastic polyester elastomer material with excellent flame retardancy can be obtained without a very high addition amount.
[0053] Furthermore, the ingredients of the thermoplastic polyester elastomer material are preferably 80-120 parts of thermoplastic polyester elastomer, 2-12 parts of modified POSS and its derivative flame retardant synergist, 4-7 parts of P series flame retardant, and 4-7 parts of N series flame retardant in parts by weight.
[0054] Reducing the amount of phosphorus-based flame retardants and nitrogen-based flame retardants can further improve the mechanical properties of thermoplastic polyurethane elastomer materials.
[0055] Further, the thermoplastic polyester elastomer includes at least one of polyester-type thermoplastic polyester elastomer and polyether-type thermoplastic polyester elastomer.
[0056] In some embodiments, the thermoplastic polyester elastomer is preferably a polyester-type thermoplastic polyester elastomer.
[0057] Furthermore, the P series flame retardant includes an inorganic phosphorus flame retardant or an organic phosphorus flame retardant, the inorganic phosphorus flame retardant includes at least one of red phosphorus, phosphate, and polyphosphate; the organic phosphorus flame retardant includes at least one of phosphate ester, phosphite, phosphonate, and phosphine oxide; and / or, the N series flame retardant includes at least one of melamine urate, melamine phosphate, and melamine inorganic acid salt.
[0058] It is understood that the phosphorus-based flame retardant includes, but is not limited to, aluminum hypophosphite, calcium hypophosphite, diethyl aluminum phosphite, methyl ethyl aluminum hypophosphite and phenyl aluminum hypophosphite.
[0059] In some embodiments, the P-based flame retardant is preferably aluminum diethylphosphinate.
[0060] In some embodiments, the N-series flame retardant is preferably melamine cyanurate.
[0061] Furthermore, the ingredients of the thermoplastic polyester elastomer material also include at least one of a lubricant and an antioxidant; wherein, the ingredients are calculated by weight, the lubricant is 0.5-1 part, and the antioxidant is 0.5-1 part.
[0062] Lubricants can improve the fluidity of thermoplastic polyester elastomer resins, reduce the coefficient of friction, make the product surface smoother, improve processing efficiency, and improve the transparency and gloss of plastics; antioxidants can effectively reduce the oxidation rate of materials during processing and use by capturing free radicals, decomposing peroxides and complexing metal ions, thereby delaying or preventing oxidation or auto-oxidation processes, protecting plastic products from oxidation and extending their service life.
[0063] In some embodiments, the lubricant includes but is not limited to at least one of a silicone lubricant, PE wax, PP wax, a fatty acid, and a fatty acid salt, and the lubricant is preferably PE wax.
[0064] In some embodiments, the antioxidant includes but is not limited to at least one of a hindered phenol antioxidant, a hindered amine antioxidant, and a phosphate antioxidant. The antioxidant is preferably antioxidant 1010.
[0065] In order to solve the above problems, the present invention also provides a method for preparing a thermoplastic polyester elastomer material, comprising the following steps: S1: Dehydration reaction to obtain modified POSS and its derivative flame retardant synergist; S2: The ingredients are mixed evenly, and the mixture is subjected to internal kneading, extrusion and granulation to obtain granular materials; the granular materials are dried to obtain a thermoplastic polyester elastomer material.
[0066] In some embodiments, extrusion granulation is achieved by a twin-screw extruder.
[0067] In some embodiments, the temperature of the thermoplastic polyester elastomer material obtained by extrusion pelletization is 170°C-190°C.
[0068] Furthermore, the dehydration reaction obtains the modified POSS and its derivative flame retardant synergist, comprising the following steps: dissolving compound 1 in an organic solvent solution, adding an aqueous solution of compound 2 under the action of a catalyst, performing a catalytic reaction, and then washing and drying to obtain the modified POSS and its derivative flame retardant synergist.
[0069] In some embodiments, the drying time is preferably 8-12 hours.
[0070] The content of the present invention is explained below through specific examples and data.
[0071] The information of the raw materials involved in the specific implementation is shown in Table 1: Table 1 Information of raw materials of Examples and Comparative Examples
[0072] The thermoplastic polyurethane elastomer materials obtained in the above examples and comparative examples were injection molded or molded, and flame retardant grade, oxygen index, tensile strength, elongation at break, 110°C heat shock, 130°C heat shock, 150°C heat shock tests were performed. The test standards are as follows: (1) Flame retardant grade test In accordance with GB / T 5455-2014, the specimens are subjected to vertical burning grade test, the specimens are cut to the specified size and tested under conditions, and key parameters such as burning time limit and residual substances are monitored.
[0073] (2) Whether there is dripping when testing the flame retardant grade Whether there is dripping when testing the flame retardancy level is tested according to the UL94 standard, the sample thickness is 3mm, and the test temperature is 23±2℃. The test is carried out using the UL94 vertical combustion test device of Jiangsu Zhengrui Taibang Electronics Co., Ltd.
[0074] (3) Oxygen index According to GB / T 2406.2-2009, the sample size is prepared according to the type IV sample. The test is carried out according to method A-top surface ignition method. The test is carried out using the oxygen index tester device of Nanjing Jiangning District Fangshang Analytical Instrument Equipment Factory.
[0075] (4) Tensile strength and elongation at break The test was conducted in accordance with Article 9 of GB 1040-2008, the test temperature was 23±2℃, and the tensile test used a standard dumbbell-shaped specimen with a tensile speed of 250mm / min. The tensile strength and elongation at break of 5 specimens were tested using a micro-controlled electronic universal material tensile machine from Dongguan High-speed Railway Testing Co., Ltd., and the results were averaged.
[0076] (5) 110-150℃ thermal shock The test was carried out in accordance with Appendix A of GB / T 32129-2015, with a test temperature of 23±2°C and a weight of 2kg. Three samples were tested at each temperature using the thermal shock test device of Hebei Zhongke Beigong Testing Instrument Co., Ltd.
[0077] The test results are shown in Table 3.
[0078] Embodiment 1: 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 ml of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped, vacuum rotary evaporation was performed, water was added for washing, and drying was performed to obtain a modified POSS flame retardant synergist 1; 90 parts of DuPont 4556 polyether thermoplastic polyester elastomer, 10 parts of modified POSS flame retardant synergist 1, 3 parts of P series flame retardant, 3 parts of N series flame retardant, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic polyester elastomer preform, and then dried at 80°C to obtain a highly flame retardant and crack-resistant thermoplastic polyester elastomer material for charging cables.
[0079] Embodiment 2: The preparation method is the same as that of Example 1, except that: 50 parts of DuPont 4556 polyether thermoplastic polyester elastomer, 12 parts of modified POSS flame retardant synergist 1, 5 parts of P series flame retardant, 3 parts of N series flame retardant, 0.5 parts of lubricant, and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic polyester elastomer preform, and then dried at 80°C to obtain a highly flame retardant and crack-resistant thermoplastic polyester elastomer material for charging cables.
[0080] Embodiment 3: The preparation method is the same as that of Example 1, except that: 90 parts of DuPont 4556 polyether thermoplastic polyester elastomer, 2 parts of modified POSS flame retardant synergist 1, 3 parts of P series flame retardant, 10 parts of N series flame retardant, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic polyester elastomer preform, and then dried at 80°C to obtain a highly flame retardant and crack-resistant thermoplastic polyester elastomer material for charging cables.
[0081] Embodiment 4: The preparation method is the same as that of Example 1, except that: 80 parts of DuPont 4556 polyether thermoplastic polyester elastomer, 10 parts of modified POSS flame retardant synergist 1, 10 parts of P series flame retardant, 9 parts of N series flame retardant, 0.5 parts of lubricant, and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic polyester elastomer preform, and then dried at 80°C to obtain a highly flame retardant and crack-resistant thermoplastic polyester elastomer material for charging cables.
[0082] Embodiment 5: The preparation method is the same as that of Example 1, except that: 90 parts of DuPont 4556 polyether thermoplastic polyester elastomer, 12 parts of modified POSS flame retardant synergist 1, 7 parts of P series flame retardant, 7 parts of N series flame retardant, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic polyester elastomer preform, and then dried at 80°C to obtain a highly flame retardant and crack-resistant thermoplastic polyester elastomer material for charging cables.
[0083] Embodiment 6: The preparation method is the same as that of Example 1, except that: 50 parts of DuPont 4556 polyether thermoplastic polyester elastomer, 12 parts of modified POSS flame retardant synergist 1, 7 parts of P series flame retardant, 7 parts of N series flame retardant, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic polyester elastomer preform, and then dried at 80°C to obtain a highly flame retardant and crack-resistant thermoplastic polyester elastomer material for charging cables.
[0084] Embodiment 7: The preparation method is the same as that of Example 1, except that: 80 parts of DuPont 4556 polyether thermoplastic polyester elastomer, 10 parts of modified POSS flame retardant synergist 1, 5 parts of P series flame retardant, 5 parts of N series flame retardant, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic polyester elastomer preform, and then dried at 80°C to obtain a highly flame retardant and crack-resistant thermoplastic polyester elastomer material for charging cables.
[0085] Embodiment 8: The preparation method is the same as that of Example 1, except that: 80 parts of LG Chemical KEYFLEX® BT-1033D polyester-type thermoplastic polyester elastomer, 10 parts of modified POSS flame retardant synergist 1, 3 parts of P series flame retardant, 3 parts of N series flame retardant, 0.5 parts of lubricant, and 0.5 parts of antioxidant were mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic polyester elastomer preform, and then dried at 80°C to obtain a highly flame-retardant and crack-resistant thermoplastic polyester elastomer material for charging cables.
[0086] Embodiment 9: 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 ml of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of dibenzofuran-3-boric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped. The mixture was evaporated under reduced pressure, washed with water, and dried to obtain the modified POSS flame retardant synergist 2.
[0087] 80 parts of DuPont 4556 polyether thermoplastic polyester elastomer, 10 parts of modified POSS flame retardant synergist 2, 5 parts of P series flame retardant, 5 parts of N series flame retardant, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic polyester elastomer preform, and then dried at 80°C to obtain a highly flame retardant and crack-resistant thermoplastic polyester elastomer material for charging cables.
[0088] Comparative Example 1: The preparation method is the same as that of Example 1, except that: 80 parts of DuPont 4556 polyether thermoplastic polyester elastomer, 14 parts of modified POSS flame retardant synergist 1, 5 parts of P series flame retardant, 5 parts of N series flame retardant, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic polyester elastomer preform, and then dried at 80°C to obtain a highly flame retardant and crack-resistant thermoplastic polyester elastomer material for charging cables.
[0089] Comparative Example 2: The preparation method is the same as that of Example 1, except that: 80 parts of DuPont 4556 polyether thermoplastic polyester elastomer, 10 parts of P series flame retardant, 10 parts of N series flame retardant 1, 0.5 parts of lubricant, and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic polyester elastomer preform, and then dried at 80°C to obtain a highly flame-retardant and crack-resistant thermoplastic polyester elastomer material for charging cables.
[0090] Comparative Example 3: The preparation method is the same as that of Example 1, except that: 80 parts of DuPont 4556 polyether thermoplastic polyester elastomer, 10 parts of modified POSS flame retardant synergist 1, 10 parts of N series flame retardant, 0.5 parts of lubricant, and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic polyester elastomer preform, and then dried at 80°C to obtain a highly flame retardant and crack-resistant thermoplastic polyester elastomer material for charging cables.
[0091] Comparative Example 4: The preparation method is the same as that of Example 1, except that: 80 parts of DuPont 4556 polyether thermoplastic polyester elastomer, 10 parts of modified POSS flame retardant synergist 1, 10 parts of P series flame retardant, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic polyester elastomer preform, and then dried at 80°C to obtain a highly flame retardant and crack-resistant thermoplastic polyester elastomer material for charging cables.
[0092] Comparative Example 5: The preparation method is the same as that of Example 1, except that: 80 parts of DuPont 4556 polyether thermoplastic polyester elastomer, 20 parts of modified POSS flame retardant synergist 1, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic polyester elastomer preform, and then dried at 80°C to obtain a highly flame retardant and crack-resistant thermoplastic polyester elastomer material for charging cables.
[0093] Comparative Example 6: 80 parts of DuPont 4556 polyether thermoplastic polyester elastomer, 20 parts of P series flame retardant, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic polyester elastomer preform, and then dried at 80°C to obtain a highly flame-retardant and crack-resistant thermoplastic polyester elastomer material for charging cables.
[0094] Comparative Example 7: 80 parts of DuPont 4556 polyether thermoplastic polyester elastomer, 20 parts of N series flame retardant, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic polyester elastomer preform, and then dried at 80°C to obtain a highly flame-retardant and crack-resistant thermoplastic polyester elastomer material for charging cables.
[0095] Comparative Example 8: 80 parts of DuPont 4556 polyether thermoplastic polyester elastomer, 10 parts of benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid flame retardant, 5 parts of P series flame retardant, 5 parts of N series flame retardant, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic polyester elastomer preform, and then dried at 80°C to obtain a highly flame-retardant and crack-resistant thermoplastic polyester elastomer material for charging cables.
[0096] Comparative Example 9: 80 parts of DuPont 4556 polyether thermoplastic polyester elastomer, 10 parts of aminopropyl heptaisobutyl cage polysilsesquioxane flame retardant, 5 parts of P series flame retardant, 5 parts of N series flame retardant, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic polyester elastomer preform, and then dried at 80°C to obtain a highly flame retardant and crack-resistant thermoplastic polyester elastomer material for charging cables.
[0097] Comparative Example 10: 80 parts of DuPont 4556 polyether thermoplastic polyester elastomer, 5 parts of benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid flame retardant, 5 parts of aminopropyl heptaisobutyl cage polysilsesquioxane flame retardant, 5 parts of P series flame retardant, 5 parts of N series flame retardant, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic polyester elastomer preform, and then dried at 80°C to obtain a highly flame-retardant and crack-resistant thermoplastic polyester elastomer material for charging cables.
[0098] Comparative Example 11: 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 ml of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of methylboric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped, vacuum rotary evaporation was performed, water was added for washing, and drying was performed to obtain methylboric acid modified POSS flame retardant.
[0099] 80 parts of DuPont 4556 polyether thermoplastic polyester elastomer, 10 parts of methyl boric acid modified POSS flame retardant, 5 parts of P series flame retardant, 5 parts of N series flame retardant, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic polyester elastomer preform, and then dried at 80°C to obtain a highly flame retardant and crack-resistant thermoplastic polyester elastomer material for charging cables.
[0100] Comparative Example 12: 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 ml of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of phenylboric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped, vacuum rotary evaporation was performed, water was added for washing, and drying was performed to obtain phenylboric acid modified POSS flame retardant.
[0101] 80 parts of DuPont 4556 polyether thermoplastic polyester elastomer, 10 parts of phenylboric acid modified POSS flame retardant, 5 parts of P series flame retardant, 5 parts of N series flame retardant, 0.5 parts of lubricant and 0.5 parts of antioxidant are mixed evenly, and granulated by twin-screw extrusion at 180°C to obtain a thermoplastic polyester elastomer preform, and then dried at 80°C to obtain a highly flame retardant and crack-resistant thermoplastic polyester elastomer material for charging cables.
[0102] The components and important preparation variables of Examples 1-9 and Comparative Examples 1-12 are summarized in Table 2.
[0103] Table 2 Components of Examples 1-9 and Comparative Examples 1-12 of the present invention.
[0104] According to the provisions of GB / T 1040-2008, GB / T 5455, GB / T 2406.2, GB / T32129 and UL94, the thermoplastic polyester elastomer materials in the above Examples 1-9 and Comparative Examples 1-12 were tested for tensile strength, elongation at break, flame retardancy, oxygen index, 110°C heat shock, 130°C heat shock, 150°C heat shock and dripping during combustion, and the test results were recorded in the following Table 3: Table 3 Performance test table of Examples 1-9 of the present invention and Comparative Examples 1-12 Tensile strength / MPa Elongation at break (%) Flame retardant grade Oxygen index (%) Is it dripping? 110℃ heat shock 130℃ heat shock 150℃ thermal shock Example 1 29 540 V0 25 no No cracking No cracking No cracking Example 2 24 450 V0 30 no No cracking No cracking No cracking Example 3 27 530 V0 25 no No cracking No cracking No cracking Example 4 20 405 V0 32 no No cracking No cracking No cracking Example 5 25 500 V0 30 no No cracking No cracking No cracking Example 6 18 350 V0 34 no No cracking No cracking No cracking Example 7 27 520 V0 26 no No cracking No cracking No cracking Example 8 26.5 525 V0 26 no No cracking No cracking No cracking Example 9 26 520 V0 28 no No cracking No cracking No cracking Comparative Example 1 27 490 V0 25 no No cracking No cracking No cracking Comparative Example 2 19 380 V2 24 yes Cracking Cracking Cracking Comparative Example 3 23 460 V2 20 no No cracking No cracking No cracking Comparative Example 4 22 430 V1 26 no No cracking No cracking No cracking Comparative Example 5 24 445 V2 22 no No cracking No cracking No cracking Comparative Example 6 14 280 V2 24 yes Cracking Cracking Cracking Comparative Example 7 19 400 V2 20 yes No cracking Cracking Cracking Comparative Example 8 27 565 V0 24 yes No cracking No cracking No cracking Comparative Example 9 25 543 V2 23 yes No cracking No cracking No cracking Comparative Example 10 24 525 V0 25 yes No cracking No cracking No cracking Comparative Example 11 28 575 V2 22 yes No cracking No cracking No cracking Comparative Example 12 26 560 V0 26 yes No cracking No cracking No cracking According to the above test results, it can be seen that the modified POSS flame retardant synergist 1 of the present invention is added to Examples 1-4, and the flame retardant grades are all V0, and the oxygen index is 25-32%. Examples 1-4 have good flame retardancy and high flame retardant efficiency; the number of TPEE added is changed in Example 5 and Example 6, 90 parts of TPEE are added in Example 5, and 50 parts of TPEE are added in Example 6. By comparing the experimental data of the two embodiments, it can be seen that in Example 6, when the amount of TPEE added to the substrate is large, the obtained thermoplastic polyester elastomer material has higher tensile strength and elongation at break, and its physical and mechanical properties are good, but the 30% oxygen index of Example 5 is lower than the 34% oxygen index of Example 6. It can be seen that the higher the amount of TPEE added in the substrate, the lower the content of the modified POSS flame retardant synergist, so The flame retardant properties of the obtained thermoplastic polyester elastomer are worse; the substrate added in Example 7 is polyether TPEE, and in Example 8, the added substrate is the same number of polyester TPEE. In Example 9, relative to Example 7, the structural type of the added modified POSS flame retardant synergist is changed. By comparing the experimental data in the above table, the tensile strength, elongation at break, flame retardant grade, oxygen index, 110°C thermal shock, 130°C thermal shock, 150°C thermal shock and whether dripping during combustion of Examples 7-9 are basically the same, indicating that in the present invention, the change of the substrate in the system and the change of the type of the modified POSS flame retardant synergist will not affect the performance of the prepared thermoplastic polyester elastomer material, and the modified POSS and its derivative flame retardant synergist provided by the present invention can stably improve the flame retardancy of the prepared material;In Comparative Example 1, relative to Example 7, an excessive amount of modified POSS flame retardant synergist 1 is added. The elongation at break in Comparative Example 1 is 490%, which is lower than 520% in Example 7, indicating that when an excessive amount of modified POSS flame retardant synergist is added, the physical and mechanical properties of the system will be reduced, resulting in poor plastic deformation ability of the prepared material and prone to brittle fracture. No modified POSS flame retardant synergist is added in Comparative Example 2, Comparative Example 6 and Comparative Example 7, and the flame retardant grades of the three are all V2, the tensile strength is lower than 20MPa, the elongation at break is less than 400%, and the oxygen index is less than 25%. In the dripping test during burning, the thermoplastic polyester elastomer material dripped in Comparative Examples 2, 6 and 7. Compared with Example 7, cracking occurred in Comparative Examples 2 and 6 in the tests of 110°C thermal shock, 130°C thermal shock and 150°C thermal shock. The thermoplastic polyester elastomer material of Comparative Example 7 did not crack in the test of 110°C thermal shock, but cracked in the tests of 130°C thermal shock and 150°C thermal shock. This shows that the addition of the modified POSS flame retardant synergist of the present invention can make the prepared thermoplastic polyester elastomer material have excellent flame retardancy and physical and mechanical properties without the need for a very high addition amount, and the excellent charring property of the modified POSS flame retardant synergist provides a protective layer for the thermoplastic polyester elastomer material, making The thermoplastic polyester elastomer material did not drip during the combustion process; no P series flame retardant was added in Comparative Example 3, no N series flame retardant was added in Comparative Example 4, and no P series flame retardant and N series flame retardant were added in Comparative Example 5. The elongation at break of Comparative Example 3, Comparative Example 4 and Comparative Example 5 were all less than 445%, with the lowest being 280%, and the flame retardant grades were V2, V1 and V2, respectively. Compared with Example 7, the flame retardant properties of the three were poor, indicating that the modified POSS flame retardant synergist, P series flame retardant and N series flame retardant in the present invention need to work together, and during the combustion process, the Si element can react rapidly with the C element in the R2 group to generate a large number of Si-C bonds, and at the same time, the B element can form a glass film on the surface of the thermoplastic polyester elastomer material, and the generated boric acid rapidly dehydrates the polymer to produce a carbon layer. The B element in the modified POSS synergistic flame retardant can also coordinate with the P element in the system to produce a synergistic effect, thereby improving the flame retardant effect, and the P series flame retardant provides an acid source, the N series flame retardant provides a gas source, and the modified POSS synergistic flame retardant provides a rich carbon source, so that the P series flame retardant and the N series flame retardant play a stronger flame retardant, and the three work together to achieve the excellent flame retardancy of the thermoplastic polyester elastomer material; in Comparative Examples 8, 9 and 10, the modified POSS flame retardant synergist is changed into its reactant, and the experimental data of the three cannot achieve the effect of anti-dripping during combustion, and the flame retardant performance of Comparative Example 9 is poor;In Comparative Example 11 and Comparative Example 12, the same number of methylboric acid modified POSS flame retardant synergist and phenylboric acid modified POSS flame retardant synergist are added to replace the modified POSS flame retardant synergist of the present invention, the methylboric acid modified POSS flame retardant synergist lacks the R2 group with a carbon-hydrogen ratio greater than 1, and the phenylboric acid modified POSS flame retardant synergist contains a benzene ring structure, but the flame retardant grade of Comparative Example 11 is V2, and the anti-drip effect cannot be achieved during combustion, and the flame retardant performance in Comparative Example 12 is higher, and the anti-drip effect cannot be achieved during combustion, indicating that the modified POSS flame retardant synergist containing a benzene ring structure cannot generate an effective carbon layer during the combustion process to achieve the anti-drip effect during combustion. ;
[0105] Therefore, the present invention verifies that the flame retardancy of the TPEE thermoplastic polyester elastomer material is improved by modifying the POSS flame retardant synergist, so that the material has excellent physical and mechanical properties and excellent combustion and dripping prevention effects, has extremely high industrial value, and can be widely used and promoted.
[0106] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.
Claims
1. A modified POSS and its derivative flame retardant synergist, characterized in that: The structure of the modified POSS and its derivative flame retardant synergist is: Wherein, R is a non-reactive group, such as isobutyl, isooctyl, ethyl, cyclohexyl, cyclopentyl, or phenyl, and R1 is n-propyl or phenylene; R2 is a cyclic structure with a carbon-to-hydrogen ratio greater than 1, including at least one of a benzofuran group and a polycyclic aromatic group.
2. The modified POSS flame retardant synergist as claimed in claim 1, characterized in that The benzofuran group includes at least one of a benzofuran group and a dibenzofuran group.
3. The modified POSS flame retardant synergist as claimed in claim 1, characterized in that The polycyclic aromatic group includes at least one of a naphthalene ring group, an anthracene ring group, a phenanthrene ring group, an acenaphthene ring group, a fluorene ring group and a perylene ring group.
4. A method for synthesizing a modified POSS and its derivative flame retardant synergist, prepared by dehydration reaction of compound 1 and compound 2 under the action of a catalyst, characterized in that: The reaction route is as follows:
5. The method for synthesizing the modified POSS and its derivative flame retardant synergist as claimed in claim 4, characterized in that: Firstly, the compound 1 is dissolved in an organic solvent solution, and then a catalyst is added. Under the action of the catalyst, an aqueous solution of the compound 2 is added, and after a catalytic reaction, the solution is washed and dried to obtain a modified POSS and its derivative flame retardant synergist.
6. The method for synthesizing the modified POSS and its derivative flame retardant synergist as claimed in claim 4, characterized in that: The molar ratio of compound 1 to compound 2 is 2:
1.
7. The method for synthesizing the modified POSS and its derivative flame retardant synergist as claimed in claim 4, characterized in that: The catalyst includes at least one of an acidic catalyst, a metal catalyst, a basic catalyst and an organic catalyst, and the solvent is an organic solvent, including at least one of alcohols, aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, ethers, ketones and diol derivatives.
8. A thermoplastic polyester elastomer material, characterized in that: The ingredients of the thermoplastic polyester elastomer material, measured in parts by weight, include: 80-120 parts of thermoplastic polyester elastomer, 2-12 parts of the flame retardant synergist of modified POSS and its derivatives as described in claims 1-7, P series flame retardant 1-10 parts, 1-10 parts of N series flame retardant.
9. A thermoplastic polyester elastomer material according to claim 8, characterized in that: The ingredients of the thermoplastic polyester elastomer material, measured in parts by weight, include: 80-120 parts of thermoplastic polyester elastomer, 2-12 parts of the flame retardant synergist of modified POSS and its derivatives as described in claims 1-7, 4-7 parts of P series flame retardant, 4-7 parts of N series flame retardant.
10. The thermoplastic polyester elastomer material according to claim 8, characterized in that The thermoplastic polyester elastomer includes at least one of a polyester-type thermoplastic polyester elastomer or a polyether-type thermoplastic polyester elastomer.
11. The thermoplastic polyester elastomer material according to claim 8, characterized in that The P series flame retardant includes an inorganic phosphorus flame retardant or an organic phosphorus flame retardant, wherein the inorganic phosphorus flame retardant includes at least one of red phosphorus, phosphate, and polyphosphate; the organic phosphorus flame retardant includes at least one of phosphate, phosphite, and phosphine oxide; And / or, the N series flame retardant includes at least one of melamine urate, melamine phosphate, and melamine inorganic acid salt.
12. The thermoplastic polyester elastomer material according to claim 8, characterized in that The ingredients of the thermoplastic polyester elastomer material also include at least one of a lubricant and an antioxidant; wherein, in terms of weight, the lubricant is 0.5-1 part, and the antioxidant is 0.5-1 part.
13. A method for preparing a thermoplastic polyester elastomer material as claimed in claim 8, characterized in that: The following steps are involved: The modified POSS and its derivative flame retardant synergist are obtained by dehydration reaction; The ingredients are mixed uniformly, and twin-screw extrusion granulation is performed to obtain granular materials; the granular materials are dried to obtain the thermoplastic polyester elastomer material.
14. The method for preparing a thermoplastic polyurethane elastomer material according to claim 13, characterized in that: The ingredients also include at least one of a lubricant and an antioxidant.
Citation Information
Patent Citations
A rubber molding method and rubber
CN111269362B
Cited By
Eleven-layer co-extrusion film, preparation process and application in aviation cable
CN121608434A